2018
DOI: 10.1515/ijnsns-2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Legendre Wavelets for Solving Variable-Order Fractional Nonlinear Advection-Diffusion Equation with Variable Coefficients

Abstract: This article studies a numerical scheme for solving two-dimensional variable-order time fractional nonlinear advection-diffusion equation with variable coefficients, where the variable-order fractional derivative is in the Caputo type. The main idea is expanding the solution in terms of the 2D Legendre wavelets (2D LWs) where the variable-order time fractional derivative is discretized. We describe the method using the matrix operators and then implement it for solving various types of fractional advection-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In the current work, two important types of radial basis functions, the generalized multiquadric and thin plate spline functions are used as basis functions in the relation (12). The thin plate splines (TPS), (r) = r 2m ln(r), m = 1, 2, 3, … , are strictly conditionally positive definite radial functions and belong to C 2m−1 .…”
Section: Spatial Discretization By the Methods Of Approximate Particulmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current work, two important types of radial basis functions, the generalized multiquadric and thin plate spline functions are used as basis functions in the relation (12). The thin plate splines (TPS), (r) = r 2m ln(r), m = 1, 2, 3, … , are strictly conditionally positive definite radial functions and belong to C 2m−1 .…”
Section: Spatial Discretization By the Methods Of Approximate Particulmentioning
confidence: 99%
“…is used as the basis function in (12), too. In the GMQ function, the exponent q and the shape parameter c play important rules to improve the accuracy and stability of the radial basis interpolation or collocation techniques.…”
Section: Spatial Discretization By the Methods Of Approximate Particulmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several studies for solving the variable-order (VO) fractional differential equation (FDE). Li et al [23] solved VO FDE model of shape memory polymers, Dehestani et al [24] proposed pseudo-operational matrix method for the solution of VO FPIDEs, Doha et al [25] employed spectral technique for solving VO fractional Volterra integro-differential equations (VIDEs), Babaei et al [26] suggested Sinc collocation method for the numerical solution of VO FIPDEs, Heydari et al [27] presented LWs optimization method for solving VO fractional Poisson equation, and Hosseininia et al [28] proposed 2-D LWs for solving VO fractional nonlinear advection-diffusion equation with variable coefficients.…”
mentioning
confidence: 99%